2014
DOI: 10.1186/1755-8794-7-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis reveals disease-associated genes and biomarkers for prostate cancer progression

Abstract: BackgroundProstate cancer is one of the most common complex diseases with high leading cause of death in men. Identifications of prostate cancer associated genes and biomarkers are thus essential as they can gain insights into the mechanisms underlying disease progression and advancing for early diagnosis and developing effective therapies.MethodsIn this study, we presented an integrative analysis of gene expression profiling and protein interaction network at a systematic level to reveal candidate disease-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 84 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…We observed no significant difference in gene expression between mock and NCsiRNA treated cells. EGFR siRNA treatment inhibited expression of EGFR (4.4 fold), IGF1 (17.8 fold) and ESR1 (4.52 fold vs. NCsiRNA expression) genes, that have been described earlier with respect of EGFR signaling [18][19][20][21]. Similarly, the RFE-siEGFR treatment inhibited EGFR (2.4 fold), IGF1 (13.7 fold) and ESR1 (4.4 fold, Fig.…”
Section: Rfe Gene Knockdownmentioning
confidence: 51%
“…We observed no significant difference in gene expression between mock and NCsiRNA treated cells. EGFR siRNA treatment inhibited expression of EGFR (4.4 fold), IGF1 (17.8 fold) and ESR1 (4.52 fold vs. NCsiRNA expression) genes, that have been described earlier with respect of EGFR signaling [18][19][20][21]. Similarly, the RFE-siEGFR treatment inhibited EGFR (2.4 fold), IGF1 (13.7 fold) and ESR1 (4.4 fold, Fig.…”
Section: Rfe Gene Knockdownmentioning
confidence: 51%
“…Interestingly, also enriched under androgen deprivation, as well as with androgen treatment, were several other members of the ETS family of transcription factors (Fig 8A and S12A Fig). In the presence of androgens, the most enriched motif corresponded not to ELK1 but to SP1, an AR-interacting protein upregulated in prostate cancer (S12A Fig) [42]. SP1 is reported to promote AR target gene expression in response to androgens and to occupy sites near gene promoters [43, 44].…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that -216 SNP in the EGFR promoter was associated with altered promoter activity by Sp1 binding and gene expression both in vitro and in vivo (72). SP1 has been shown to directly or indirectly regulate some PCa related genes, of which EGFR is one (73). …”
Section: Discussionmentioning
confidence: 99%